Neogene diatoms at DSDP Leg 55 Holes - Itaru Koizumi (PANGAEA, 1980)
Leg 55 of the Deep Sea Drilling Project started from Honolulu, Hawaii, on 23 July 1977 and terminated at Yokohama, Japan on 6 September, 1977. Eleven holes were drilled at 4 sites; a multiple re-entry hole was drilled on Suiko Seamount. As originally planned, Leg 55 had two objectives: (1) drilling at least two sites on the Emperor Seamount chain, and (2) drilling a third site in Mesozoic Pacific crust in anomaly M-l on the oceanic side of the Kuril trench. The proposed site in Mesozoic crust, however, was abandoned for logistical reasons. Because the principal objective of Leg 55 was to test the "hot-spot" hypothesis of the origin of the Hawaiian and Emperor chains, the recovery of sedimentary sequences for diatoms was not of primary importance. Drilling on Suiko Seamount (Site 433), however, yielded pelagic sediments which consist mostly of skeletons of diatoms, radiolarians, and foraminifers, without the terrigenous material such as sand, silt, and volcanic ash. Eighty-two samples from the 11 holes drilled on Leg 55 were examined for diatoms. The entire upper Neogene section of the northernmost site (433) contains abundant and moderately well preserved diatoms. Regrettably, diatoms are very rare throughout the samples from Quaternary sediments of the southern sites (Sites 430 to 432), owing to the lower primary production in the warm-water area; no diatoms were recovered in any samples from sediments older than lower Neogene from the northernmost site.
Supplement to: Koizumi, I (1980): Neogene diatoms from the Emperor Seamount Chain, Leg 55, Deep Sea Drilling Project. In: Jackson, E.D.; Koisumi, I.; et al., Initial Reports of the Deep Sea Drilling Project, 55, Initial Reports of the Deep Sea Drilling Project, 55, U.S. Government Printing Office, 55, 387-407, https://doi.org/10.2973/dsdp.proc.55.113.1980